ANALISIS NERACA AIR UNTUK PENETAPAN PERIODE TANAM TANAMAN PANGAN DI PROPINSI BANTEN (ANALYSIS OF WATER BALANCE FOR DETERMINE GROWING PERIODS OF FOOD CROPS IN BANTEN PROVINCE) - T. Hidayat; Yonny Kusmaryono; A. Pramudia (Agromet, 2006)
Growing periods can be determined using water balance analysis to decrease harvest risk in certain area. Generally, there are two types of land use for crop, irrigated land and non-irrigated land. The experiment aims to determine growing periods of food crop in Banten Province. Modified method of Thornthwaite and Mather of bookkeeping system of water balance has been used base on decades data. Water balance analysis of irrigated land showed that in the area of Serang District has growing periods potencially of 140-170 days with growing periods starting from Dec2 till Jan1, but necessary need water supply from irrigation as amount 8.5-22.5 mm to growing rise twice a year or planted with other food crops after rice if no irrigation. Meanwhile in Tangerang District (Pakuhaji) and Pandeglang District (Pagelaran) has potency of 182-193 days of growing periods with starting on Sep3 at Pakuhaji and on Dec3 at Pagelaran. In these area rice can be planted twice a year without irrigation. Futhermore, for non-irrigation/land with monthly high rainfall, the analysis indicated that the area has potency of growing periods of 182 days as even through the year. Planting dates can be started from Oct1 till Dec1, with sequence of rice-rice or rice-rice-other food crops.